The machinist [videorecording (DVD)] - Anderson, Brad, 1964-; Bale, Christian, 1974-; Leigh, Jennifer Jason, 1962-; Sánchez-Gijón, Aitana (Paramount Home Entertainment, 2005)
Trevor Reznik hasn't slept in a year. The shocking deterioration of his physical and mental health has made his every waking moment an unrelenting state of confusion, paranoia, guilt, anxiety and terror. His only solace from this living nightmare comes from an affectionate prostitute. When cryptic notes turn up mysteriously in his apartment and hallucinations of a co-worker that no one else sees causes a gruesome machine shop injury, he embarks on a journey to find out whether there is an elaborate plot to drive him mad or his fatigue has simply robbed him of reason.